ORGANIC RANKINE CYCLE (ORC) SYSTEM IN RENEWABLE AND SUSTAINABLE ENERGY DEVELOPMENT: A REVIEW OF THE UTILIZATION AND CURRENT CONDITIONS FOR SMALL-SCALE APPLICATION - Hijriawan, Miftah; Himawanto, Dwi Aries; Pambudi, Nugroho Agung; Arifin, Zainal (Journal of Applied Engineering Science, 2022)
The Organic Rankine Cycle (ORC) is a thermodynamic cycle that converts heat into mechanical energy to produce electrical power in a closed system using organic working fluids. It is also a heat recovery technology that can use heat at low temperatures and makes it a promising thermodynamic cycle with cost-effectiveness and more energy efficiency. However, the ORC system’s total efficiency is determined by the compatibility of the expander characteristics and working fluid properties with the system’s thermodynamic cycle parameters. This study aims to analyze using an integrative review method regarding the development of the ORC system as a heat recovery technology. The purpose of the integrative review method is to review the knowledge base, where the review is carried out critically and has the potential to conceptualize and expand the theoretical foundation developed. In this case, the first analysis is about the literature study on the parameters of the ORC system. Furthermore, the development and optimization of the ORC system are discussed further to analyze its capabilities in various applications. Work fluids, component optimizations, and system configurations have been reported for possible improvements. In addition, this ORC system can be used as a technology in developing various renewable energy sources, including solar, biomass, geothermal, and waste heat. Furthermore, this system is assessed for its environmental and economic benefits to developing its capabilities and potential. The results show that integrating the ORC system in various renewable energy sources can provide proper operation, better efficiency, and advantages such as increased power and reduced pollution.